Root litter diversity and functional identity regulate soil carbon and nitrogen cycling in a typical steppe. (February 2020) - Man, Jing; Tang, Bo; Xing, Wen; Wang, Yang; Zhao, Xuezhen; Bai, Yongfei
Abstract: Root litter decomposition is the dominant source of soil organic carbon (C) and nitrogen (N) in grasslands. Few studies, however, have explored the effect of root litter diversity on soil C and N cycling. This study investigated the effects of species diversity and functional traits of root litter on soil CO2 and N2 O release, net ammonification, net nitrification, and net N mineralization based on a 56-day incubation of grassland soils with root litter mixtures containing one, two, or four native plant species. The increasing species richness of root litter decreased the cumulative CO2 and N2 O release in the soil, but enhanced the net ammonification, nitrate immobilization, and N mineralization. Root litter diversity has a predominant non-additive antagonistic effect on the release of soil CO2 and N2 O, and a synergistic effect on the net ammonification, nitrate immobilization, and N mineralization in the soil. The functional identity rather than functional diversity of root traits explains most of the variation in soil C and N cycling. A high C: N ratio and low concentrations of N, P, K, and Di-O-alkyl-C (characteristic of celluloses) were found to be key to the antagonistic effects associated with cumulative release of CO2 from the soil. For net N ammonification and mineralization, the synergistic effect was principally induced by the high levels of carbohydrate-C and N and the low C: N ratios in root litter mixtures. Our study highlights the role and mechanisms of increased root litter diversity in decreasing soil CO2 and N2 O release and in increasing the net N mineralization via non-additive antagonistic and synergistic effects of dominant root traits. Graphical abstract: Image 1 Highlights: High root litter diversity decreases cumulative CO2 and N2 O release in the soil. Great root litter diversity increases soil net N ammonification and mineralization. The decreasing soil CO2 release is caused by antagonistic effects of root traits. Root litter diversity regulates soil N cycling via synergistic effects of root traits. Functional identity explains more than functional diversity in soil C and N cycles.